The Importance of Being Oroonoko: An Art Historical Morality Play. Issue 4 (18th November 2021) - Pop, Andrei
Abstract: Since Gert Schiff's magisterial publication of 1973 on Henry Fuseli (1741–1825), a print identified as representing the enslaved prince Oroonoko has raised unsettling questions about the complex implication of even liberal, abolitionist eighteenth-century artists and intellectuals in the world system of enslaved labor. But problems of fit with Thomas Southerne's 1695 play Oroonoko, popular throughout the eighteenth century, and with Aphra Behn's 1688 eponymous novel demand a reattribution, placing the print in a debate about not only slavery in the Americas but also race, classicism, and the merits of Indigenous and European civilization in South Africa.